2001
DOI: 10.1130/0091-7613(2001)029<0591:meoyky>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mountain erosion over 10 yr, 10 k.y., and 10 m.y. time scales

Abstract: We used cosmogenic 10 Be to measure erosion rates over 10 k.y. time scales at 32 Idaho mountain catchments, ranging from small experimental watersheds (0.2 km 2) to large river basins (35 000 km 2). These long-term sediment yields are, on average, 17 times higher than stream sediment fluxes measured over 10-84 yr, but are consistent with 10 m.y. erosion rates measured by apatite fission tracks. Our results imply that conventional sediment-yield measurements-even those made over decades-can greatly underestimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
393
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(416 citation statements)
references
References 33 publications
20
393
1
2
Order By: Relevance
“…Wittmann et al (2007) observed such underestimates for the Central Alps by comparing river loads with cosmogenic nuclide-derived denudation rates (figs 2B and 2C). Underestimates possibly arose because of the lack of inclusion of solute and bedload transport, sediment trapping by retention dams, or because the time span during which suspended load concentrations have been measured is too short to sample the high-magnitude floods that are considered to be the most effective mechanisms for sediment discharge (Kirchner et al, 2001;Molnar, 2001;Dadson et al, 2003). Despite these drawbacks, the data show a consistent pattern that is characterized by an increase in denudation rates from <0.02 mm/yr in the foreland to >0.1 mm/yr in the Alpine core.…”
Section: Suspended Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wittmann et al (2007) observed such underestimates for the Central Alps by comparing river loads with cosmogenic nuclide-derived denudation rates (figs 2B and 2C). Underestimates possibly arose because of the lack of inclusion of solute and bedload transport, sediment trapping by retention dams, or because the time span during which suspended load concentrations have been measured is too short to sample the high-magnitude floods that are considered to be the most effective mechanisms for sediment discharge (Kirchner et al, 2001;Molnar, 2001;Dadson et al, 2003). Despite these drawbacks, the data show a consistent pattern that is characterized by an increase in denudation rates from <0.02 mm/yr in the foreland to >0.1 mm/yr in the Alpine core.…”
Section: Suspended Loadsmentioning
confidence: 99%
“…A similar pattern of denudation rates, although with slightly different magnitudes, resulted from the 1993 survey. It is important to note here that the use of suspension load measurements over a short time period can often result in substantial underestimates of sediment transfer (e.g., Kirchner et al, 2001;Schaller et al, 2001). Wittmann et al (2007) observed such underestimates for the Central Alps by comparing river loads with cosmogenic nuclide-derived denudation rates (figs 2B and 2C).…”
Section: Suspended Loadsmentioning
confidence: 99%
“…This, in turn, is a prerequisite for the development of appropriate catchment management strategies aimed at minimizing their negative effects on water quality, water treatment costs [Holmes, 1988] and ecological and human health. Fluvial sediment fluxes are also used to diagnose climatic and tectonic influences upon landscape denudation and evolution [e.g., Kirchner et al, 2001;Cornwell et al, 2003;Major, 2004;Ferrier et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions that drive sediment inputs may be impossible to discern using measured spatial and temporal sequences at smaller scales (Kirchner et al, 2001), yet knowledge of factors controlling their frequency and magnitude, the spatial extent of affected stream channels, and spatial synchrony between basins is crucial to anticipating affects of land management and climate change on aquatic ecosystems (Reeves et al, 1995, Dunham et al, this issue).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The regime of sediment inflows can be difficult to characterize, in part because of the extended periods that may separate large-magnitude events (Kirchner et al, 2001). Yet, as discussed above, this regime forms an integral component of a river ecosystem (Reeves et al, 1995;Gresswell, 1999), and any changes to that regime pose consequences that are largely unknown.…”
Section: Introductionmentioning
confidence: 99%